Carbon-Encapsulated Co3O4@CoO@Co Nanocomposites for Multifunctional Applications in Enhanced Long-life Lithium Storage, Supercapacitor and Oxygen Evolution Reaction. (1st December 2016) - Xu, Dongyang; Mu, Congpu; Xiang, Jianyong; Wen, Fusheng; Su, Can; Hao, Chunxue; Hu, Wentao; Tang, Yongfu; Liu, Zhongyuan
Graphical abstract: Abstract: Porous nanostructure composites materials had attracted widely attention due to their potential application in energy storage (Lithium ion batteries (LIBs) and supercapacitor) and electrocatalyst of oxygen evolution reaction (OER). Co3 O4 @CoO@Co@C nanocomposites had been successfully synthesized using glucose as carbon source and cobalt nitrate as metalprecurs or of Co3 O4 @CoO@Co@C, which has excellent electrochemical performance for LIBs, supercapacitor and OER. Three kinds of morphology samples marked by Co3 O4 @CoO@Co@C-2/1, Co3 O4 @CoO@Co@C-1/1 and Co3 O4 @CoO@Co@C-1/2 are synthesized due to different atomic ratio of cobalt/carbon in precursors. Electrochemical and catalytic performance of Co3 O4 @CoO@Co@C-2/1 nanocomposites is more excellent than Co3 O4 @CoO@Co@C-1/1 and Co3 O4 @CoO@Co@C-1/2. Co3 O4 @CoO@Co@C-2/1 shows that discharge capacity can maintain 450 mA h g −1 and coulombic efficiency is nearly 100% during 500 cycles for LIBs. It indicates the excellent cycling stability of Co3 O4 @CoO@Co@C-2/1 as electrode for supercapacitor that about 78.3% of initial specific capacitance can be retained after 10000 cycles at current density of 2 A g −1 . Co3 O4 @CoO@Co@C-2/1 as catalyst of OER shows excellent electrochemical durability over 15 hours continuous experiment.